2017
DOI: 10.1007/s00109-017-1600-y
|View full text |Cite
|
Sign up to set email alerts
|

Plasma circular RNA profiling of patients with gastric cancer and their droplet digital RT-PCR detection

Abstract: A total of 343 circRNAs are differentially expressed between gastric cancer patients' plasma and healthy controls. Hsa_circ_0001017 and hsa_circ_0061276 are downregulated in gastric cancer tissues. The RT-ddPCR is a potent method for simultaneous detection of multiple circRNAs in plasma. Hsa_circ_0001017 and hsa_circ_0061276 are potential biomarkers for gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
171
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 221 publications
(174 citation statements)
references
References 33 publications
3
171
0
Order By: Relevance
“…Among the included publications, a total of 43 articles on 64 studies were analyzed involving 10,123 subjects in Table . Of the 64 studies, five studies focused on colorectal cancer (Ji et al, ; Wang, Li, et al, ; Wang et al, ; Zhang, Yang, et al, ; Zhuo, Lin, Chen, Huang, & Hu, ), 10 on breast cancer (Lu et al, ; Yin et al, ), 22 on gastric cancer (Chen, Li, Zhao, Xiao, & Guo, ; Huang, He, Liang, Huang, & Zhu, ; Li, et al, , ; Li, Shao, et al, ; Li, Song, et al, ; Lu et al, ; Lu, Shao, Ye, Xiao, & Guo, ; Shao, Chen, et al, ; Shao, Li, et al, ; Shao, Yang, et al, ; Sun, Tang, et al, ; Tian, Chen, Li, & Xiao, ; Wei et al, ; Xie et al, ; Zhao, Chen, Li, Xiao, & Zhang, ), four on lung cancer (Li, Wang, Chen, Chen, & Jin, ; Zhu et al, ; Zong et al, ), 16 on hepatocellular carcinoma (Chen, Zhang, Lin, Song, & Wang, ; Fu et al, , ; Li et al, ; Qin et al, ; Shang et al, ; Yao et al, ; Yao et al, ; Zhang, Zhang, Lin, & Wang, ; Zhang, Zhou, et al, ; Zhang, Xu, et al, ) and seven on other cancers (Fan, Cao, Liu, Zhang, & Li, ; Lan et al, ; Li et al, ; Sun, Li, et al, ; Teng et al, ; Wang, Xue, et al, ; Yang et al, ). Moreover, three articles with 13 studies explored the diagnostic value of the combined circRNAs (Chen, Li, Zhao, et al, ; Fan et al, ; Li, Shao, et al, ) in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the included publications, a total of 43 articles on 64 studies were analyzed involving 10,123 subjects in Table . Of the 64 studies, five studies focused on colorectal cancer (Ji et al, ; Wang, Li, et al, ; Wang et al, ; Zhang, Yang, et al, ; Zhuo, Lin, Chen, Huang, & Hu, ), 10 on breast cancer (Lu et al, ; Yin et al, ), 22 on gastric cancer (Chen, Li, Zhao, Xiao, & Guo, ; Huang, He, Liang, Huang, & Zhu, ; Li, et al, , ; Li, Shao, et al, ; Li, Song, et al, ; Lu et al, ; Lu, Shao, Ye, Xiao, & Guo, ; Shao, Chen, et al, ; Shao, Li, et al, ; Shao, Yang, et al, ; Sun, Tang, et al, ; Tian, Chen, Li, & Xiao, ; Wei et al, ; Xie et al, ; Zhao, Chen, Li, Xiao, & Zhang, ), four on lung cancer (Li, Wang, Chen, Chen, & Jin, ; Zhu et al, ; Zong et al, ), 16 on hepatocellular carcinoma (Chen, Zhang, Lin, Song, & Wang, ; Fu et al, , ; Li et al, ; Qin et al, ; Shang et al, ; Yao et al, ; Yao et al, ; Zhang, Zhang, Lin, & Wang, ; Zhang, Zhou, et al, ; Zhang, Xu, et al, ) and seven on other cancers (Fan, Cao, Liu, Zhang, & Li, ; Lan et al, ; Li et al, ; Sun, Li, et al, ; Teng et al, ; Wang, Xue, et al, ; Yang et al, ). Moreover, three articles with 13 studies explored the diagnostic value of the combined circRNAs (Chen, Li, Zhao, et al, ; Fan et al, ; Li, Shao, et al, ) in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, several studies provided that single circRNAs in combination with other plasma protein biomarkers such as CEA, CA‐15.3, CA‐125 and AFP possess better diagnostic performance (Huang et al, ; Prefumo, ; Yang et al, ; Yin et al, ; Zhang, Yang, et al, ). Additionally, a single circRNA combined with other circRNAs obtained also had better diagnostic accuracy (Li, Chen, et al, ; Li, Shao, et al, ; Ren & Xin, ). For example, Li et al identified that has_circ_0000096 and hsa_circ_002059 have moderate diagnosis value for gastric cancer, with an AUC of 0.82 and 0.73 respectively, while the AUC value of hsa_circ_0000096 combined with hsa_circ_002509 increased to 0.91 (Li, et al, , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The qRT‐PCR products were confirmed by Sanger sequencing, which was completed by Geneseed. The relative quantification levels of hsa_circ_0067582 were calculated using the ΔC q (quantification cycle) method . A higher ΔC q value indicated a lower expression level .…”
Section: Methodsmentioning
confidence: 99%
“…A single peak in the melting curve indicated the specificity of qRT‐PCR results. The data were analyzed using the Δ C q method . And the expression of circRNAs in cells was analyzed by the 2 −ΔΔ C q method.…”
Section: Methodsmentioning
confidence: 99%